Public Procurement Outcomes: Aligning Process, Policy, and Impact - Ahmari, Dhafer Al; Brika, Said K. (Journal of Posthumanism, 2025)
This analysis of public procurement outcomes research, based on Scopus data from 1976 to December 2023, provides valuable insights into the thematic structure, trends, and collaborative networks within the field. By mapping PPO’s intellectual landscape, this study identifies core themes and developments in sustainable procurement, public-private partnerships, and e-procurement practices. A thorough bibliometric investigation—based on co-citation, keyword analysis, and thematic clustering—was accomplished with the software VOSviewer and Biblioshiny and brought to light linkages between respondents and institutions in relation to various research themes. The analysis of 582 Scopus-indexed publications provides a significant sense of clustering around themes such as “public procurement in construction” or “sustainable procurement," which suggests that there is a tendency or that this is direction-specific focused on environmentally oriented, market demand, and policy-influenced procurement practices. For example, LOVE PED and CHAN APC emerged as key players with strong networks based in the UK, USA and Australia. The regional breakdown exposed variations within the research focus, which indicated disparities in policy and development concerns. During the last 10 years, the research activity in this field has drastically increased, and some manuscripts have been published in the International Journal of Procurement Management, Journal of Cleaner Production, and Public Money and Management, among others. Despite these findings, a restrictive collaboration network exists among authors and institutions, with a marked North-South divide, suggesting limited cooperation between developed and developing nations. Topic modeling revealed essential themes—innovation, corruption, green procurement, procurement contracts, and SMEs—providing a foundation for future research directions that emphasize enhanced international collaboration, green procurement impacts, and nuanced policy analyses across various levels